Spatial Urban – Rural Interaction Patterns in Metropolitan Cirebon Raya using Remote Sensing and Socioeconomic Data - Zahrul Atharinafi; Nurrohman Wijaya (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2021)
Urbanization patterns in developing Asian countries may or may not follow commonly known urbanization patterns and models set forth by lessons from the developed world. A unique phenomenon described as desakota is well known as a unique artifact of Asian urbanization, in which new urban areas arise semi-independently from otherwise rural regions in proximity to the edges of continuous urbanized areas.. We intend to identify the interaction between the urban fringe and surrounding rural areas while taking unique socioeconomic and morphological characteristics of the Desakota into account. We utilize a combination of K - Means Clustering, factor analysis and spatiotemporal analysis to identify patterns of urbanization in Metropolitan Cirebon Raya, an industrializing metropolitan statistical region where agriculture is still a douse, around Cirebon City, using statistical socioeconomic and demographic data from Badan Pusat Statistik in addition to land use data obtained from Landsat. Between 2010 – 2020, we identified substantial desakota type growth, in which new urbanized land development occurred organically from a formerly rural area, weakly linked to the supposed ‘center’ of the specified metropolitan region (Metropolitan Cirebon Raya). Based on the results obtained, we were able to corroborate desakota theory through quantitative methods, by taking socioeconomic and demographic data into account as a supplement to land use data. For delineation of metropolitan regions in Southeast Asia in which desakota patterns of development are presumed, we recommend utilizing the methodology we have developed, integrating both socioeconomic and demographic data to better identify desakota regions in peri-urban regions.